Starch biosynthesis, its regulation and biotechnological approaches to improve crop yields - Bahaji, Abdellatif; Li, Jun; Sánchez-López, Ángela María; Baroja-Fernández, Edurne; Muñoz, Francisco José; Ovecka, Miroslav; Almagro, Goizeder; Montero, Manuel; Ezquer, Ignacio; Etxeberria, Ed; Pozueta-Romero, Javier (Biotechnology advances, 2014)
Structurally composed of the glucose homopolymers amylose and amylopectin, starch is the main storage carbohydrate in vascular plants, and is synthesized in the plastids of both photosynthetic and non-photosynthetic cells. Its abundance as a naturally occurring organic compound is surpassed only by cellulose, and represents both a cornerstone for human and animal nutrition and a feedstock for many non-food industrial applications including production of adhesives, biodegradable materials, and first-generation bioethanol. This review provides an update on the different proposed pathways of starch biosynthesis occurring in both autotrophic and heterotrophic organs, and provides emerging information about the networks regulating them and their interactions with the environment. Special emphasis is given to recent findings showing that volatile compounds emitted by microorganisms promote both growth and the accumulation of exceptionally high levels of starch in mono- and dicotyledonous plants. We also review how plant biotechnologists have attempted to use basic knowledge on starch metabolism for the rational design of genetic engineering traits aimed at increasing starch in annual crop species. Finally we present some potential biotechnological strategies for enhancing starch content.
Keywords: Genetic engineering; MIVOISAP; zemědělské plodiny; Starch futile cycling; biotechnologie; Crops, Agricultural; Carbohydrate metabolism; škrob; Calvin–Benson cycle; Metabolic Networks and Pathways; Sucrose synthase; Endocytosis; metabolické sítě a dráhy; Starch; Microbial volatiles; Plant–microbe interaction; ADPglucose; Biotechnology